Improving virtual reality - Allen, John, 1957- (Real-world STEM., 2018)
Describes the development of virtual reality, and examines how engineers and scientists are working to improve virtual reality and use it to solve real-world problems. Includes a timeline of engineering achievements, color photographs, and further resources.